Co-creation as a lens to analyze citizen participation in active mobility - Lima, Jailene Aparecida Vieira; Paulino , Sonia (Technical and Scientific Journal Green Cities, 2025)
Objective – Analyze citizen participation through the co-creation of solutions for pedestrian mobility. Methodology – Literature review (2019–2025) on social innovation in public services (ISSP) and co-creation applied to active/pedestrian mobility, with emphasis on Brazil/Latin America, using searches in Scopus and Web of Science. Originality/Relevance – This article addresses how citizen participation—focusing on co-creation—contributes to the design and implementation of pedestrian-mobility solutions in cities in developing countries, particularly São Paulo and other Latin American cities. It discusses the tension between the temporary nature of tactical urbanism and the conditions of continuity and stabilization required by social innovation in public services. Results – Citizen participation manifests as co-creation throughout the social-innovation cycle—diagnosis, design, implementation, and evaluation. We systematize mechanisms/factors that support the transition from tactical interventions to permanent solutions: formal regulatory frameworks that convert pilots into policy, organizational capacities, and governance arrangements. Theoretical/Methodological Contributions – Analyzes citizen participation, via co-creation, in developing pedestrian-mobility solutions in São Paulo, in dialogue with recent evidence from Latin America. Social and Environmental Contributions – Provides inputs for public policies and co-creation practices that foster the consolidation of active-mobility initiatives.